Screening of Sclerotinia stem rot resistance in Bangladesh mustard germplasm using cotyledon assay method - Naher, Najmun; Shamsi, Shamim; Ali, Md Rawshan; Bashar, Md Abul (Dhaka University Journal of Biological Sciences, 2018)
In the present investigation Brassica germplasm were screened in vitro against Sclerotinia sclerotiorum, the causal organism of stem rot disease of mustard (Brassica spp.) using cotyledon assay. The germplasm belong to Brassica rapa, B. juncea, B napus and Brassica sp. Among the 81 germplasm and seven cultivated varieties seven genotypes, namely BD 10113, BD 6948, BD 6954, BD 7108, BD7121, BD 7788 and BD7799 exhibited resistant reaction and eight germplasm viz. JBC 05117, BD 10456, BD6974, BD7116, BD7802, BD7804, BD7806, and BD7807 expressed moderately resistant reaction against S. sclerotiorum. The rest 66 germplasm and showed susceptibility at varied degree. Moderately susceptible reaction was observed in 29, susceptible in 26 and highly susceptible reaction was found in 11 germplasm. Out of seven cultivated varieties three were found highly susceptible, two were susceptible and two showed moderately susceptible. Dhaka Univ. J. Biol. Sci. 27(1): 85-92, 2018 (January)